PERSEPSI PEGAWAI TERHADAP GAYA KEPEMIMPINAN ATASAN LANGSUNG DI BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN SIJUNJUNG - Ferdy (Universitas Negeri Padang, 2014)
This study phenomena in the background shows the implementation of the direct supervisor's leadership style not apply to employees in good BAPPEDA. This study is intended to obtain information about an employee's perception of the immediate supervisor's leadership style BAPPEDA Sijunjung district in improving the performance of duties an employee-oriented leadership style and task-oriented leadership style subordinates. The population is 36 BAPPEDA of civil servants Sijunjung district. Samples taken were 100% of the total population of 36 people. The instrument used in this study is a questionnaire that has been sampled validity and reliability. In general, an employee's perception of the supervisor's leadership style directly in the performance of duties in BAPPEDA Sijunjung district in the category quite well with the overall average score was 3.2 with 74.1% achievement rate. Kata kunci: leadership style